The Use of Preview, Question, Read, Summarize, Test (PQRST) Strategy to Improve Students’ Reading Comprehension in Recount Text - Dimas Anom (Universitas Lancang Kuning, 2018)
The research aims to know the effectiveness of the PQRST strategy in students’ reading comprehension. This research was classroom action research (CAR). This study design by 4 meetings and one result with 3 hours of learning. The subjects were the first grade students of TKJ Department SMKN 05 Pekanbaru consisted of 35 students. Qualitative data were collected by using observation sheets for the researcher and the students, field notes and interview. Then, the quantitative data were collected by reserving in table, graphic, and diagram. After conducting this research using PQRST strategy, researcher got based score was 65 and final scoring 79. The based score was 65 to 79 with increasing point was 14 point. The quantitative data were analyzed by scoring the results of reading comprehension tests and then the results of scoring were calculated to find out the central tendency (mean) for describing improvement of each indicator of reading comprehension in each cycle. During the one cycle, the results of quantitative analysis were related to the results of qualitative analysis in order to explain the factors that cause the improvement qualitatively, The factors increase students ‘reading comprehension included teacher, team work and strategy. Based on result, Researcher concluded that PQRST can improve the students’ reading comprehension.